Practical endocrinology and diabetes in children - Donaldson, Malcolm D. C. (John Wiley & Sons, Incorporated, 2019)
The fourth edition of Practical Endocrinology and Diabetes in Children offers a practical, highly clinical handbook of paediatric endocrinology and diabetes. The book is written in clear terms and offers a user-friendly format that is designed to be concise, yet comprehensive. The international panel of expert contributors explore the range of endocrine disorders in children including growth, thyroid, adrenal and problems related to puberty. Each chapter is updated to reflect the latest developments. The fourth edition also contains key web links, guidelines and courses for endocrinologists and paediatricians, case studies and more suggestions for avoiding errors. In addition, the handbook includes a new chapter on hormones and genetics and considers conditions of care in countries with limited resources. This revised fourth edition: Offers a practical handbook that is highly readable and designed in a user-friendly format; Contains more explicit reference to North American and global guidelines; Includes contributions from an international team of experts; Presents tips and ideas for avoiding errors. Written for the practising paediatrician, Practical Endocrinology and Diabetes in Children bridges the gap between the large, detailed endocrine reference book and a short review of aspects of endocrinology.